Migraine and the trigeminovascular system—40 years and counting - Ashina, Messoud (Lancet Neurol, 2019)
The underlying causes of migraine headache remained enigmatic for most of the 20th century. In 1979, The Lancet published a novel hypothesis proposing an integral role for the neuropeptide-containing trigeminal nerve. This hypothesis led to a transformation in the migraine field and understanding of key concepts surrounding migraine, including the role of neuropeptides and their release from meningeal trigeminal nerve endings in the mechanism of migraine, blockade of neuropeptide release by anti-migraine drugs, and activation and sensitisation of trigeminal afferents by meningeal inflammatory stimuli and upstream role of intense brain activity. The study of neuropeptides provided the first evidence that antisera directed against calcitonin gene-related peptide (CGRP) and substance P could neutralise their actions. Successful therapeutic strategies using humanised monoclonal antibodies directed against CGRP and its receptor followed from these findings. Nowadays, 40 years after the initial proposal, the trigeminovascular system is widely accepted as having a fundamental role in this highly complex neurological disorder and provides a road map for future migraine therapies.